Performance of Ag/Al2O3 catalysts in the liquid phase oxidation of glycerol – effect of preparation method and reaction conditions. Issue 9 (16th December 2015) - Skrzyńska, E.; Zaid, S.; Addad, A.; Girardon, J.-S.; Capron, M.; Dumeignil, F.
Abstract : A series of silver supported catalysts have been developed and proposed for mild oxidation of glycerol in the liquid phase. High selectivity to glycolic acid, stability in both continuous-flow and periodic mode of reaction, and good resistance to crude glycerol impurities have been achieved. Abstract : This paper presents a systematic study of alumina supported silver catalysts, a novel catalytic system proposed for the liquid phase aerobic partial oxidation of glycerol to glycolic acid, the smallest α-hydroxyacid with numerous industrial applications (raw material in the chemical industry, ingredient in textiles, food, cosmetics, plastics, adhesives, pharmaceuticals, etc. ). We evaluated the effect of the preparation method, the silver loading and the type of alumina support on the properties and the activity of the solids. We showed that numerous parameters can affect the catalytic performances, the most important of which were the following: the type of solvent used during preparation, the basicity and phase composition of the support, as well as the amount of base used during glycerol oxidation. The most active catalysts were at the same time the most selective ones to glycolic acid, which clearly differentiates the silver catalysts from other noble metals conventionally used in glycerol oxidation, such as Au, Pd and Pt, characterized by a high selectivity to glyceric acid. The best results in terms of conversion and selectivity to glycolic acid were obtained over the catalyst prepared by the chemical reduction method in a basic methanol solution, using formaldehyde as a reductant. After 3 h of reaction at 60 °C under 5 bar of oxygen pressure over such a catalyst loaded with 3.6 wt% Ag, an 85% glycerol conversion together with a 57.1% selectivity to glycolic acid were achieved. Moreover, the catalysts showed good stability in the continuous mode and very good resistance to the impurities present in a crude glycerol fraction.